2020
DOI: 10.21043/iqtishadia.v13i2.7626
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Muslim Religiosity and Innovation Capability on Firm Survival: A Study on Small Enterprises During the Covid-19 Pandemic

Abstract: <p>This research aimed to examine and analyze the effect of Muslim religiosity and innovation capability on firm survival. Also, this research investigated the moderation role of environmental uncertainty on the effect of Muslim religiosity and innovation capability on firm survival. The study was conducted during the covid-19 pandemic. The analysis unit of this research was the owners of processed food small enterprises fostered by the regional government of Bantul Regency, Yogyakarta. The number of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
3
11
0
1
Order By: Relevance
“…The results also show that a combination of high CBA, OIC and REC improves SMEs’ survival strategies even in the absence of MES during the pandemic. These findings are in accordance with those of Gerald et al (2020), Kuckertz et al (2020), Lin et al (2020), Utomo (2020), Kristinae et al (2020), Jiang and Wen (2020) and Giones et al (2020). The previous studies have identified SMEs’ CBA, OIC and RCE, such that solutions (recipes) explain the model, thereby leading these firms’ survival strategies during the COVID-19 pandemic.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The results also show that a combination of high CBA, OIC and REC improves SMEs’ survival strategies even in the absence of MES during the pandemic. These findings are in accordance with those of Gerald et al (2020), Kuckertz et al (2020), Lin et al (2020), Utomo (2020), Kristinae et al (2020), Jiang and Wen (2020) and Giones et al (2020). The previous studies have identified SMEs’ CBA, OIC and RCE, such that solutions (recipes) explain the model, thereby leading these firms’ survival strategies during the COVID-19 pandemic.…”
Section: Resultssupporting
confidence: 87%
“…The results also indicate that SME’s survival strategy during COVID-19 results from the interactions of multiple conditions; and establish causal symmetry, which refers that all five antecedents significantly influence SME’s survival strategy during COVID-19 that characterised the relationship amongst the antecedents of SME’s survival strategy during COVID-19. This finding also supports that among all antecedents, SME’s business agility and innovation capability strongly influence to SME’s survival strategy during COVID-19, which also further supports previous research findings (Gerald et al , 2020; Vidmar et al , 2020; Utomo, 2020; Wanasida et al , 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Constraints in paying bank loan installments amid a decline in demand for furniture orders This data illustrates that most MSME players (78%) undertake strategic steps by making innovations in producing products and services to survive the crisis caused by the Covid-19 pandemic. This is consistent with results of the study in Yogyakarta of Utomo (2020) that the ability of SME's innovation may improve firm survival during Covid-19 pandemic.…”
Section: Furniture Trading Micro-equity and Bank Loan (Kur)supporting
confidence: 92%
“…They used religion and spirituality to cope with their mental and physical health. It is assumed that religion plays a pivotal role in the life of entrepreneurs in times of the COVID-19 crisis ( 80 ).…”
Section: Discussionmentioning
confidence: 99%